2023
DOI: 10.1177/08902070231174575
|View full text |Cite
|
Sign up to set email alerts
|

Do you mind a closer look? A jingle-jangle fallacy perspective on mindfulness

Abstract: Mindfulness is defined inconsistently, and its various measures resemble established personality self-report scales. Therefore, jingle and jangle fallacies are likely to undermine the construct’s utility. To address these issues, we conducted two studies to test three hurdles of validity: 1) a sound definition and measurement model, 2) empirical distinctiveness, and 3) incremental criterion validity. We established an overarching and inclusive mindfulness definition covering twelve aspects. Based on this defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
2
7
1
Order By: Relevance
“…A. Baer et al, 2008), our explanation based on the items’ contents appears more robust and consistent with previous investigations, such as the study by Rudkin et al (2018). Additionally, another alternative hypothesis could involve neuroticism playing a confounding role, as suggested by the comprehensive analysis conducted by Altgassen et al (2023), which compared mindfulness scales and personality factors, in particular neuroticism. However, our findings seem to highlight the significant influence of external or sensitive stimulations in shaping the correlation between awareness and psychological distress, as predicted by SPS, rather than emotional awareness and dysregulation, which a stronger role of neuroticism would imply.…”
Section: The Devil Is In Details: Assessing Mindfulness and Sensory-p...supporting
confidence: 87%
See 1 more Smart Citation
“…A. Baer et al, 2008), our explanation based on the items’ contents appears more robust and consistent with previous investigations, such as the study by Rudkin et al (2018). Additionally, another alternative hypothesis could involve neuroticism playing a confounding role, as suggested by the comprehensive analysis conducted by Altgassen et al (2023), which compared mindfulness scales and personality factors, in particular neuroticism. However, our findings seem to highlight the significant influence of external or sensitive stimulations in shaping the correlation between awareness and psychological distress, as predicted by SPS, rather than emotional awareness and dysregulation, which a stronger role of neuroticism would imply.…”
Section: The Devil Is In Details: Assessing Mindfulness and Sensory-p...supporting
confidence: 87%
“…This finding is consistent with the analysis conducted by Rudkin et al (2018), who also concluded that the Observing scale of the FFMQ emphasizes a higher number of items related to external sensations and bodily awareness compared to emotional awareness. Furthermore, Altgassen et al (2023) found an unsatisfactory factor structure for mindfulness constructs derived from wellestablished mindfulness scales such as the FFMQ and PHLMS. Additionally, it is noteworthy that only a limited number of items across these three scales are dedicated to evaluating interoceptive or body awareness, with the majority of items primarily focusing on the impact of external sensations on present-moment awareness, neglecting the comprehensive assessment of internal bodily experiences (Bishop et al, 2004).…”
Section: A Brief Review Of Studies On the Relationship Between Mindfu...mentioning
confidence: 99%
“…In the case of intelligence mindsets, we need to know whether and how this link is present in challenging situations. As beliefs about mindfulness skills is a sparsely investigated field, detailed future research is needed regarding how the mindfulness mindset construct fits into the large family of mindfulness-related constructs that are not always strongly related to relevant real-life outcomes above and beyond already examined personality variables (e.g., Altgassen et al, 2023).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Measures of dispositional mindfulness were created to provide an operationalization of what changes in mindfulness-based programs (see e.g., Baer, 2011). However, as an intervention with an ambiguous theoretical background, it may not be surprising that there is very little empirical support for dispositional or trait mindfulness as a psychological construct, nor is their adequate evidence to suggest dispositional mindfulness is the core mechanism by which mindfulness-based programs have their effects (Altgassen et al, 2023;Goldberg et al, 2019;Van Dam et al, 2018). Existing psychological constructs with a stronger theoretical and empirical basis, such as emotion regulation and decentering, may do a better job explaining how mindfulness meditation improves mental health than dispositional mindfulness (see, e.g., Goldberg et al, 2019).…”
Section: Mindfulness and Contemplative Practicesmentioning
confidence: 99%